Postrelease Survival and Migration Behavior of Adult Walleye Following Intracoelomic Transmitter Implantation Using Two Methods of Electro‐Immobilization. Issue 1 (13th December 2021) - Reid, Connor H.; Faust, Matthew D.; Raby, Graham D.; Brenden, Travis O.; Cooke, Steven J.; Vandergoot, Christopher S.
Abstract: The use of electricity as a method of fish restraint (i.e., electro‐immobilization) during field and hatchery operations has increased recently, and a need exists for field‐based assessments of the effects of these techniques on the postrelease physiology, behavior, and survival of wild fish to develop best handling practices. Two common waveforms used in electro‐immobilization are continuous and pulsed DC (cDC and pDC, respectively). With cDC, fish are immobilized through exposure to a continuous weak current and recover almost immediately once the current ceases. With pDC, fish are incapacitated via brief exposure to a strong current and often require several minutes to recover (i.e., regain equilibrium). Here, we present a comparison of cDC and pDC electro‐immobilization techniques and their effects on the postrelease survival and spawning migration behavior of adult Walleye Sander vitreus in a Lake Erie tributary. Fish were intracoelomically implanted with acoustic transmitters and then tracked by a network of acoustic receivers throughout Lake Erie that provided extensive spatiotemporal coverage of posttagging movements. Survival did not differ between the two electro‐immobilization treatments but was somewhat lower than in a control group consisting of fish tagged several years earlier (e.g., 50‐d survival = 69% for the pDC group, 61% for the cDC group, and 90% for control fish). We did not find any plausible or biologically meaningful effects of treatment on downstream movement or migratory behavior over subsequent months postrelease. Our results suggest that the two electro‐immobilization techniques did not differ in their effects on adult Walleye behavior, but more work is needed to elucidate the extent to which electro‐immobilization in general contributes to potential decreases in survival versus other aspects of capture and handling associated with performing surgical procedures.